Non-random mating behaviour between diverging littoral and pelagic three-spined sticklebacks in an invasive population from Upper Lake Constance - Tobias Zeidler; Albert Ros; Samuel Roch; Arne Jacobs; Juergen Geist; Alexander Brinker (Royal Society Open Science)
Adaptive divergence and increased genetic differentiation among populations can lead to reproductive isolation. In Lake Constance, Germany, a population of invasive three-spined stickleback (Gasterosteus aculeatus) is currently diverging into littoral and pelagic ecotypes, which both nest in the littoral zone. We hypothesized that assortative mating behaviour contributes to reproductive isolation between these ecotypes and performed a behavioural experiment in which females could choose between two nest-guarding males. Behaviour was recorded, and data on traits relevant to mate choice were collected. Both females of the same and different ecotypes were courted with equal vigour. However, there was a significant interaction effect of male and female ecotypes on the level of aggression in females. Littoral females were more aggressive towards pelagic males, and pelagic females were more aggressive towards littoral males. This indicates rejection of males of different ecotypes in spite of the fact that littoral males were larger, more intensely red-coloured and more aggressive than the pelagic males—all mating traits female sticklebacks generally select for. This study documents the emergence of behavioural barriers during early divergence in an invasive and rapidly diversifying stickleback population and discusses their putative role in facilitating reproductive isolation and adaptive radiation within this species.